CircRNA-miRNA-VEGFA: an important pathway to regulate cancer pathogenesis - Zhang, Lei; Zhang, Yuan; Li, Xin; Gao, Huijuan; Chen, Xiatian; Li, Peifeng (Frontiers in Pharmacology, 2023)
Cancers, especially malignant tumors, contribute to high global mortality rates, resulting in great economic burden to society. Many factors are associated with cancer pathogenesis, including vascular endothelial growth factor-A (VEGFA) and circular RNAs (circRNA). VEGFA is a pivotal regulator of vascular development such as angiogenesis, which is an important process in cancer development. CircRNAs have covalently closed structures, making them highly stable. CircRNAs are widely distributed and participate in many physiological and pathological processes, including modulating cancer pathogenesis. CircRNAs act as transcriptional regulators of parental genes, microRNA (miRNA) / RNA binding protein (RBP) sponges, protein templates. CircRNAs mainly function via binding to miRNAs. CircRNAs have been shown to influence different diseases such as coronary artery diseases and cancers by regulating VEGFA levels via binding to miRNAs. In this paper, we explored the origin and functional pathways of VEGFA, reviewed the current understanding of circRNA properties and action mechanisms, and summarized the role of circRNAs in regulating VEGFA during cancer pathogenesis.